Onychopapilloma: a single medical center experience in Southern Taiwan - Po-Ta Lai; Yung-Wei Chang; Shang-Hung Lin (Taylor & Francis Group, 2024)
AbstractBackground: Onychopapilloma is an uncommon benign tumor of the nail bed and the distal matrix. Objectives: We aimed to investigate the clinical and pathological features of onychopapilloma in Taiwan.Materials and methods: We conducted a retrospective analysis of 12 patients with histopathologically proven onychopapilloma in a medical center in southern Taiwan from 2017 to 2023. Results: This case series consisted of 5 men and 7 women aged 29 to 38, with a mean age of 41.25 years. The clinical features were as follows: distal subungual hyperkeratosis (100%), longitudinal erythronychia (50%), longitudinal leukonychia (50 %), distal onycholysis (41%), and distal nail plate fissuring (41%). The duration of the disease varied greatly, ranging from 1 month to several years. Most patients were asymptomatic (58%), while some presented tenderness (41%). Fingernail involvement was more prevalent than toe involvement, with the thumb being the most commonly affected site. Most of the patients presented with a solitary onychopapilloma. None of the seven patients who underwent surgery and were available for follow-up experienced recurrence.Conclusions: This study highlights that longitudinal erythronychia and leukonychia emerged as the predominant clinical presentations of onychopapilloma. Furthermore, our findings suggest that surgical excision appears to be an effective method for onychopapilloma.